Impact of Synergistic Association of ZnO-Nanorods and Symbiotic Fungus Piriformospora indica DSM 11827 on Brassica oleracea var. botrytis (Broccoli) - Singhal, Uma; Khanuja, Manika; Prasad, Ram; Varma, Ajit (Frontiers in Microbiology, 2017)
In the present work, novel nanotool called ‘nano-embedded fungus’ formed by impact of synergistic association of ZnO-nanorods and fungus Piriformospora indica DSM 11827, for growth of Brassica oleracea var. botrytis (Broccoli) is reported. ZnO nanorods were synthesized by mechanical assisted thermal decomposition process and characterized by scanning electron microscopy (SEM) for morphology, X-ray diffraction (XRD) for structural studies and UV-vis absorption spectroscopy for band gap determination. Nanoembedded fungus is prepared by optimizing ZnO-nanorods concentration (500ppm) which resulted in the increased biomass of P. indica, as confirmed by dry weight method, spore count, spread plate and microscopy techniques viz. SEM and confocal microscopy. Enhancement in B. oleracea var. botrytis is reported on treatment with nanoembedded fungus. According to the authors, this is the first holistic study focusing on the impact of ZnO nanorods in the enhancement of fungal symbiont for enhanced biomass productivity of Brassica oleracea plant.